What family physicians should know about interventional radiology? - Bander F Aldhafery (Wolters Kluwer Medknow Publications, 2020)
Interventional radiology (IR) is a rapidly evolving specialty. The minimally invasive nature of the procedures has led to a paradigm shift in treating many disease processes from conventional surgery to interventional techniques that have become the first choice and the preferred method for the treatment of peripheral vascular disease, many aortic pathologies, and venous diseases. Interventional oncology procedures have become widely available for the treatment of solid hepatic and renal tumors. This includes palliative techniques for many advanced malignancies, and fluid drainage that is exclusively performed by interventional radiologists in many hospitals all around the world. Women's health-related procedures such as uterine fibroid embolization, fallopian tube recanalization, and embolization for pelvic congestion syndrome have become attractive choices for many patients. Family physicians (FPs) are the main source of patient referral to hospitals. However, there is a notable knowledge deficiency of IR among FPs in Saudi Arabia. This may be due to poor communication between FP and IR or the lack of FP's awareness of IR procedures. This is a nonsystematic review to introduce some IR procedures to FPs pertinent to their practice to optimize patient referral and management with the use of IR services. We focused on the most commonly performed IR procedures paying special attention to their clinical indications, benefits, and alternatives.